Analisis Perilaku Biaya dan Penggunaannya dalam Keputusan Manajerial - Teguh Anderson Teguh; Jhon Piter Manurung; Gilbert Febrianto Hutabarat; Dewa Fahri Marbun; Hamonangan Siallagan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This article discusses the importance of understanding cost behavior in managerial decision making. By analyzing how costs change with changes in activity levels, managers can make better decisions regarding planning, controlling, and managing a firm’s resources. This article explains key concepts of cost behavior such as fixed cost, variable cost, and range relevance, and provides examples of their application in a business context. Implications for managerial accounting and strategic decision making are also discussed. In addition, this article highlights the importance of cost behavior analysis in the face of uncertainty and changing business dynamics. With a solid understanding of cost behavior, managers can be more adaptive in adjusting strategies and optimizing the financial performance of the firm. Case studies and numerical examples are presented to illustrate the practical application of the concepts discussed. This article is expected to provide valuable insights for managers, accountants, and decision makers in utilizing cost behavior analysis to improve managerial effectiveness and business competitiveness.